PENGARUH MINAT BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA DI MADARASAH IBTIDAIYAH NEGERI 3 NATAR KABUPATEN LAMPUNG SELATAN - Trisnawati, Trisnawati; Sodik, Jafar; Rina, Helda (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2021)
This study aims to describe the effect of student interest in learning and mathematics learning achievement of students at Madarasah Ibtidaiyah Negeri 3 Natar, South Lampung Regency. This type of research uses descriptive quantitative. The population in this study was the fifth grade students of Madarasah Ibtidaiyah Negeri 3 Natar, South Lampung Regency in the odd semester of the 2018-2019 school year. The research method used in this research is correlational analysis. Samples were obtained by using simple random sampling technique as many as 35 students from class students of Madarasah Ibtidaiyah Negeri 3 Natar, South Lampung Regency. Data was collected by giving questionnaires and PTS tests. Data analysis was carried out using the SPSS 23 program which consisted of descriptive analysis, data analysis requirements testing and hypothesis testing. The data analysis requirements test used, namely the normality test, and the linearity test. The results of this study are research that there is a significant positive influence between interest in learning on learning achievement in mathematics, which means the greater the interest in student learning, the greater the opportunity for students to excel.